Population fluctuation and capture height of Diaphorina citri in citrus orchard - Chiaradia, Luis Antônio; Milanez, José Maria; Smaniotto, Márcia Aparecida; Davila, Márcio Roberto Furlan (Revista de Ciências Agroveterinárias, 2008)
The asian citrus psyllid...